A secure routing scheme to mitigate attack in wireless adhoc sensor network. Issue 103 (April 2021) - R, Isaac Sajan; J, Jasper
Abstract: Due to the unattended nature and deployment of wireless sensors in the hostile environment, the networks are vulnerable to carousal and stretch attack that causes Denial of Service (DoS). In addition to that, the adversary may also inject bogus data into the network through compromised nodes. This cause the Base Station (BS) to take erroneous decisions and also affects the network's lifetime. To address these issues, the Base Station Controlled Secure Routing Protocol (BSCSRP) is introduced. The proposed work aims to detect the anti-nodes from safe nodes by a trust-based mechanism that secures the network from false data injection as well as provides an efficient route that is free from carousal and stretch attack. The effectiveness of BSCSRP is evaluated by comparing its performance with the existing AF-TNS, BTEM, RSA, and ERF methods.